2010
DOI: 10.4236/abb.2010.14046
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of Aspergillus terreus from dried grapes

Abstract: RAPD was used to examine the genetic variability among five isolates of Aspergillus terreus spp. Two random primers were selected for the RAPD assay PG01-5' CAGGTGTTGC 3' and PG02-5' CTGGA-CAGAC 3' (Progen Technologies). The characterization of Aspergillus terreus species have been mostly applied on the basis of morphology, phenotype and physiology. DNA Polymorphisms are based on differences in DNA sequences and have advantages over protein polymorphisms. But morphological characterization besides molecular to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Other isolates showed 0-80% similarity coefficient values ( Figure 5). These results agree with those of Lasker (2002) whose genotyped A. fumigatus isolates, and also the results of Raclasky et al (2006) and Nariasimhan and Asokan (2010).…”
Section: The T Isolatsupporting
confidence: 93%
“…Other isolates showed 0-80% similarity coefficient values ( Figure 5). These results agree with those of Lasker (2002) whose genotyped A. fumigatus isolates, and also the results of Raclasky et al (2006) and Nariasimhan and Asokan (2010).…”
Section: The T Isolatsupporting
confidence: 93%
“…Recently, it was shown that isolates of A. terreus specifically from dried grape showed significant genomic diversity based on random amplification of polymorphic DNA–PCR data, although morphological differences were not significant. 29 …”
Section: Resultsmentioning
confidence: 99%
“…showed that isolates of A. carbonarius and A. niger clustered into species groups, however, within species, strains displaying similar degrees of toxigenicity did not cluster together when characterized by RAPD techniques (Ilic et al, 2001(Ilic et al, , 2004. The profile of the Aspergillus terreus species isolated from dried grapes, analysed by RAPD, indicated great genomic diversity (Narasimhan & Asokan, 2010 carbonarius. In addition, no genotypical differences could be established between OTA producers and non-producers in all the species analysed.…”
Section: European Biodiversity Monitoringmentioning
confidence: 99%